International News Vol.8 2011 - Editor, The (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
DOI: http://dx.doi.org/10.3126/hn.v8i0.4928 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 69-70 Uploaded date: 23 June, 2011